Perancangan Visual Branding Toko Batik Werkudoro Surakarta - Wijaya, Hanzel Calvinus; Henny Lukitasari, Evelyne; Yulianto, Arif (JURNAL KEMADHA, 2024)
Batik is one of the typical Indonesian fabric motifs that is famous internationally. Surakarta is known as the Batik City because it is one of the largest batik producing cities in Indonesia. Werkudoro batik shop is one of the batik shops in Surakarta. The Werkudoro batik shop brand is not famous among Surakarta residents. This is due to the weak visual branding of the Werkudoro batik shop and the lack of promotions carried out. This work aims to produce a redesign of the visual identity, namely the logo which is applied to various applications such as stationery, merchandise, packaging, and promotional displays. Using the redesign of the visual identity and promotional media for the Werkudoro batik shop, it is expected that it will attract people's attention and be remembered so that it can build people's interest and motivation for purchasing.